Detection of tunneling events in physically defined silicon quantum dot using single-shot measurements improved by numerical treatments. (23rd November 2020) - Mizokuchi, Raisei; Tadokoro, Masahiro; Kodera, Tetsuo
Abstract: We report the detection of a single tunneling event of electrons in a physically defined silicon quantum dot system. In the measurement, we observed single-shot tunneling events in a quantum dot using a charge sensor; however, the tunneling statistics are difficult to acquire because of their weak signals. Hence, two numerical treatments using a digital filter and a change point detection technique are applied, and the latter enables precise signal detection, which is confirmed in the simulation. We expect the combination of such digital processing with integrated circuits to enable a fast qubit readout from a noisy system.